Galectin-8 enhances adhesion of multiple myeloma cells to vascular endothelium and is an adverse prognostic factor - Friedel, Myriam; Goldschmidt, Hartmut (Glycobiology, 2016)
Multiple myeloma is characterized by abnormal infiltration of malignant plasma cells into bone marrow. Testing the hypothesis that bivalent galectin-8 (Gal-8) may influence homing of myeloma cells to vascular endothelium as a key prerequisite for infiltration, we analyzed the two Gal-8 splice variants (Gal-8S, Gal-8L). They differ in the length of their linker peptide connecting the two lectin domains. Both Gal-8 isoforms bind to cells of the myeloma lines Gal-8+ MOLP-8 and Gal-8− LP-1 in a glycan-inhibitable manner. Both Gal-8 isoforms led to enhanced adhesion of myeloma cells to vascular endothelium under dynamic shear stress conditions, Gal-8L (by more than 40-fold) even stronger than Gal-8S. Additional treatment of endothelial cells with tumour necrosis factor prior to the dynamic shear stress assay entailed an almost 100-fold enhanced adhesion of myeloma cells without addition of Gal-8 variants and a further 1.5-1.7-fold enhancement by addition of Gal-8 variants. We also found that elevated expression of Gal-8 in native multiple myeloma cells is an adverse prognostic factor for overall and event-free survival using patients’ gene expression profile data of the total therapy 2 and 3 myeloma studies. Also, elevated concentrations of Gal-8 were detected (45%, 19/42 patients) in sera of multiple myeloma patients compared to those of healthy, age-matched donors. Both experimental and clinical data strongly point to the significance of Gal-8 for multiple myeloma development.
Gesehen am 29.08.2017